2017
DOI: 10.1097/fbp.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

The α2C-adrenoceptor antagonist, ORM-10921, exerts antidepressant-like effects in the Flinders Sensitive Line rat

Abstract: Depression involves deficits in monoaminergic neurotransmission. Differential roles for α2A, B and C subtypes of the α2-adrenoceptor (AR) are evident, with selective α2C-AR antagonists purported to have antidepressant and procognitive properties. However, this has not been demonstrated in a genetic animal model of depression. The role of the α2C-AR in modulating two key depression-related behaviours in the Flinders Sensitive Line (FSL) rat was studied using a dose-response analysis following subcutaneous admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 91 publications
1
20
0
Order By: Relevance
“…Acute administration of highly subtype-selective α 2C -AR antagonists, JP-1302 ( 17 ), ORM-10921 ( 18 , 21 ) and ORM-12741 ( 19 ) to Sprague Dawley and Han-Wistar rats was found to decrease immobility in the FST (see Table 2 ), providing evidence that selective α 2C -AR antagonism harbors therapeutic antidepressant effects. Although the aforementioned findings were predominantly from acute studies, we recently reported that chronic ORM-10921 reduced FST immobility time in the FSL rat, a genetic rodent model of MDD ( 21 ). Moreover, these effects were not seen with the non-selective α 2 -AR antagonist idazoxan ( 21 ).…”
Section: Therapeutic Potential Of Targeting the α 2c mentioning
confidence: 99%
See 4 more Smart Citations
“…Acute administration of highly subtype-selective α 2C -AR antagonists, JP-1302 ( 17 ), ORM-10921 ( 18 , 21 ) and ORM-12741 ( 19 ) to Sprague Dawley and Han-Wistar rats was found to decrease immobility in the FST (see Table 2 ), providing evidence that selective α 2C -AR antagonism harbors therapeutic antidepressant effects. Although the aforementioned findings were predominantly from acute studies, we recently reported that chronic ORM-10921 reduced FST immobility time in the FSL rat, a genetic rodent model of MDD ( 21 ). Moreover, these effects were not seen with the non-selective α 2 -AR antagonist idazoxan ( 21 ).…”
Section: Therapeutic Potential Of Targeting the α 2c mentioning
confidence: 99%
“…The α 2A -AR is, therefore, the main α 2 -AR regulating 5-HT release and possibly 5-HT synthesis. Nevertheless, selective antagonism of the α 2C -AR could result in meaningful increases in 5-HT release and region-specific 5-HT synthesis (e.g., provoking serotonergic behaviours in Flinders Sensitive Line (FSL) rats ( 21 )), which may be of importance in various neuropsychiatric illnesses characterized by altered serotonergic neurotransmission, such as obsessive compulsive disorder, MDD, and schizophrenia. Confirmation of these findings using highly selective α 2C -AR subtype ligands and in appropriate animal models is, therefore, warranted (e.g., FSL rats; 21 ).…”
Section: Role Of the α 2c -Ar In Regulating Key Nementioning
confidence: 99%
See 3 more Smart Citations